2013
DOI: 10.1007/s12017-013-8261-y
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Nanoparticles Attenuate Neurochemical and Neurobehavioral Deficits in Experimental Model of Huntington’s Disease

Abstract: Till date, an exact causative pathway responsible for neurodegeneration in Huntington's disease (HD) remains elusive; however, mitochondrial dysfunction appears to play an important role in HD pathogenesis. Therefore, strategies to attenuate mitochondrial impairments could provide a potential therapeutic intervention. In the present study, we used curcumin encapsulated solid lipid nanoparticles (C-SLNs) to ameliorate 3-nitropropionic acid (3-NP)-induced HD in rats. Results of MTT (3-(4,5-dimethylthiazolyl-2)-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 64 publications
0
99
0
1
Order By: Relevance
“…Such an increase has been reported with curcumin nanoparticles in a rat model of Huntington's disease, making this compound a promising therapy for this disease. 29 In the same way, the use of nanoquercetin may protect mitochondrial integrity and functions by controlling succinate dehydrogenase activity in gastric inflammation induced by ethanol in rat. 30 In our study, as free GSNO activated the same gene cluster as gENP, one may consider that the enhancement of metabolism by gENP is related to the intracellular presence of GSNO.…”
Section: Discussionmentioning
confidence: 99%
“…Such an increase has been reported with curcumin nanoparticles in a rat model of Huntington's disease, making this compound a promising therapy for this disease. 29 In the same way, the use of nanoquercetin may protect mitochondrial integrity and functions by controlling succinate dehydrogenase activity in gastric inflammation induced by ethanol in rat. 30 In our study, as free GSNO activated the same gene cluster as gENP, one may consider that the enhancement of metabolism by gENP is related to the intracellular presence of GSNO.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of rats and mice to 3NP causes selective degeneration of medium spiny neurons in the striatum and associated motor symptoms similar to those of patients with HD . Rats treated with curcumin were relatively resistant to 3NP-induced striatal damage and exhibited preservation of mitochondrial function compared with vehicle-treated rats exposed to 3NP (Sandhir et al, 2014) 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) was originally identified as a contaminant of heroin that was responsible for the rapid development of PD-like symptoms in several young drug users. MPTP causes a highly selective degeneration of dopaminergic neurons in the substantia nigra of mice and monkeys and has therefore been widely used to model PD in these animals (Duan and Mattson, 1999;Maswood et al, 2004) Treatment of mice with curcumin protected dopaminergic neurons against MPTP-induced degeneration by a mechanism involving reduced inflammation (Ojha et al, 2012).…”
Section: B Environmental Toxicantsmentioning
confidence: 99%
“…(Family Zingiberaceae) has anti-inflammatory and antioxidant properties (Motterlini et al, 2000). Curcumin has been found to have neuroprotective effects in Alzheimer's disease, stroke, head trauma (Cole et al, 2007), alcohol-induced neurotoxicity (Kandhare et al, 2012), Huntington's disease (Sandhir et al, 2013). Curcumin also shown to have an antioxidant effects in different models of epilepsy including kainic acid induced model of epilepsy, amygdala kindling and postkindled model of epilepsy (Agarwal et al, 2011;Choudhary et al, 2013;Du et al, 2009;Gupta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%